THE EFFECTIVENESS OF THE FAMILY HOPE PROGRAM (PKH) IN REDUCING POVERTY IN SONOMARTANI VILLAGE, KUALUH HULU SUB-DISTRICT, NORTH LABUHAN BATU DISTRICT - Febby Amelia Tarigan; R. Sally Marisa Sihombing (Yayasan Wayan Marwan Pulungan, 2025)
The Family Hope Program is a conditional social assistance program that aims to reduce poverty and break the chain of intergenerational poverty. The Family Hope Program has been launched by the government since 2007. The Family Hope Program is managed by the Ministry of Social Affairs, with strict supervision by the National Development Planning Agency. The number of The Family Hope Program recipients in Sonomartani Village continues to increase from year to year, in line with the government's efforts to expand the scope of this program to improve community welfare. With this program, the community has been helped but has not changed the poverty rate. The research method in this study is descriptive qualitative research. Data was collected through interviews, observations, and documentation. Data analysis was carried out qualitatively with the Effectiveness theory approach according to Campbell J.P, namely (1) Program Success, (2) Goal Success, (3) Satisfaction with the Program, (4) Input and Output Levels, (5) Achievement of Overall Goals. The results of this study show that: (1) The stages of achieving the objectives of PKH implementation in Sonomartani Village have been carried out well and are in accordance with the objectives of PKH Implementation in Sonomartani Village, (2) PKH participants in Sonomartani Village until now still always receive assistance according to the amount according to the procedures that have been set previously, without the slightest deduction in accordance with applicable regulations.